КЛИНИКО-ЛАБОРАТОРНАЯ ХАРАКТЕРИСТИКА ХРОНИЧЕСКИХ ГЕПАТИТОВ И ЦИРРОЗОВ ПЕЧЕНИ РАЗЛИЧНОЙ ЭТИОЛОГИИ - А. Р. Билалова; В. В. Макашова (SINAPS LLC, 2015)
The review of literature discusses the clinical and biochemical changes in patients with chronic hepatitis C, chronic hepatitis of alcoholic etiology, chronic hepatitis combined genesis (HCV + alcohol) and cirrhosis in the outcome of hepatitis, liver cirrhosis complications.